Eruption Time of Premolars in Children at Urban Schools of Lahore, Pakistan (Medical Forum Monthly, 2024)
Objective: The purpose of this study was to ascertain mean eruption ages of premolars in local school children and to compare with other population groups.Study Design: cross sectional studyPlace and Duration of Study: This study was conducted in the Deptt. Of Oral Maxillofacial Surgery, KEMU, Lahore from 17.12.2009 to 17.12.2010.Materials and Methods: The mean eruption ages of permanent teeth were derived from a cross sectional study of 4000 public and private schools children in Lahore with ages ranged 8-13 years. Children were from all classes of socioeconomic status. Sample was examined in good torchlight and emergence through the gingivae was noted. Results: Maxillary premolars erupted earlier than the mandibular ones in both genders. The mean sequence of eruption in upper and lower arch was P1, P2. Maxillary 1st premolar was the first tooth to erupt in boys and girls; whereas mandibular 2nd premolar was the last one.Conclusion: (1) The premolars erupted slightly earlier than the standards used in our practice of text books. (2) Maxillary premolars erupted earlier than mandibular premolars. (3) Local standards should be applied while planning preventive and interceptive orthodontic measures and treatment modalities in other specialties.